2021
DOI: 10.1016/j.ccell.2021.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1/L1 lead-in before MAPK inhibitor combination maximizes antitumor immunity and efficacy

Abstract: Highlights d Prior ICT is associated with longer PFS of melanoma patients treated with MAPKi d Anti-PD-1/L1 before MAPKi combination prolongs durability of tumor regression d Targeting M2-TAMs augments and CD8 + T cells abolishes priming-associated benefit d Anti-PD1/L1 plus anti-CTLA-4 priming may further control melanoma brain metastasis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 34 publications
3
72
0
Order By: Relevance
“…In support of this, the Src inhibitor dasatinib was recently proposed as a pharmacological on/off switch to control CAR T cell activity transiently and reduce its lethal toxicities [ 43 ]. Additionally, a sequential versus combinatorial treatment regimen of anti-PD-1/PD-L1 lead-in before a MAPK inhibitor was shown to maximize antitumor immunity and efficacy in murine models of melanoma, colorectal, and pancreatic cancer [ 44 ]. Clinically, fulvestrant was well tolerated when previously combined with the first-generation EGFR TKIs gefitinib [ 45 ] and erlotinib [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, the Src inhibitor dasatinib was recently proposed as a pharmacological on/off switch to control CAR T cell activity transiently and reduce its lethal toxicities [ 43 ]. Additionally, a sequential versus combinatorial treatment regimen of anti-PD-1/PD-L1 lead-in before a MAPK inhibitor was shown to maximize antitumor immunity and efficacy in murine models of melanoma, colorectal, and pancreatic cancer [ 44 ]. Clinically, fulvestrant was well tolerated when previously combined with the first-generation EGFR TKIs gefitinib [ 45 ] and erlotinib [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, BRAFi-resistant tumours are cross-resistant to ICB due to ERK reactivation and subsequently enhanced MAPK pathway transcriptional output, which establishes an immunosuppressive environment with dysfunctional dendritic cells [35]. Interestingly, preclinical studies have shown that a lead-in treatment with ICB, before MAPKi, maximizes antitumour immunity and efficacy [36,37].…”
Section: Melanoma and The Problem Of Therapy Resistancementioning
confidence: 99%
“…Identifying combination strategies that may enhance the durable immunologic response will improve clinical outcomes for NSCLC patients. Recent pre-clinical studies have highlighted the potential role of MEK inhibitor combinations that affect the immune cell landscape 3 , 4 or where tumor MAPK activation drives an immune-evasive tumor microenvironment, 5 indicating a potential role for MEK inhibitors outside of the targeted agent landscape.…”
Section: Main Textmentioning
confidence: 99%
“…Recent pre-clinical work by Wang et al. 4 found that initial treatment with immunotherapy followed by MAPK inhibition optimized anti-tumor response and lead to immune cell reinvigoration. Future studies should focus on the dosing of MEKi that is necessary for CXCL10 induction and further assess which biomarkers best indicate the time point and order when immunotherapy should be given versus MEKi.…”
Section: Main Textmentioning
confidence: 99%